Maksimalisasi Keuntungan Pada Usaha Dagang Martabak Sucipto Menggunakan Metode Simpleks Dan POM-QM - Ong, Rico; Maran, Alfionita N R; Lapik, Ardianto Rizki; Andita, Dimas M B; Kadir, Muhammad Fitra; Kindangen, Ricky V; Latul, Velly B; Rumetna, Matheus Supriyanto; Lina, Tirsa Ninia (STMIK Budi Darma, 2019)
Martabak trading business is one of the businesses in the culinary field, which seeks to make the survival of the Martabak trade business can continue to develop. To maintain the continuity and development of Martabak's trading business steps are needed to be able to allocate raw materials and increase profits. Therefore, a technique or a method is needed in determining the right combination of products made and combinations of products produced. Simplex method is a method used in this research and utilizes information technology, namely the use of POM-QM tools to estimate the maximum profit gained from each production made by Martabak traders within one day quickly and accurately, so that it has an accurate calculation estimate. The result of the calculation of the maximum profit in one day is IDR 90,000.-.